Linux socket programming - Walton, Sean (Sams, 2001)
This book teaches readers how to program Linux sockets, and gives them everything they need to know to make programs communicate effetively over networks. It presents a comprehensive discussion of all relevant topics including: writing programs compatible with both Internet Protocol version 4 (IPv4) and IPv6, raw sockets, User Datagram Protocol (UDP), broadcasting /multicasting, server internals, and more, plus a section covering Posix threads. It provides thorough coverage of programming with the TCP, UDP, and IP protocols, as well as lower-level raw sockets. The myriad of function calls, data structures, and options associated with the APIs are explained with well-chosen diagrams and tables. After reading this book, the reader will be able to: Differentiate basic datagrams vs. streaming sockets. Differentiate unicast, broadcast, and multicast sockets. Write socket-based network programs. Write portable code for various OS'. Implement client-server and peer communications Increase network throughput using "connectionless" communications Manage asynchronous I/O, I/O and multiple sockets. Use signals, threading and processes to manage socket connections. Understand new socket technologies like Mbone and 6bone. Understand Remote Procedure Calls and how to implement them. Understand the different socket addressing types